Instinct : a novel - Hough, Jason M. (Skybound Books / Gallery Books, 2021)
"Welcome to Silvertown, Washington. Population: 602. (For now.) Officer Mary Whittaker is the lone cop in a small, bizarre mountain town that has yet to fully welcome her. With the chief of police on leave, she is left to uncover the truth behind a sudden spate of abnormal incidents. An exemplary, beloved teenager has died tragically after eating wild mushrooms from his lawn. A hiker was found dead on a trail, smiling serenely after being mauled by a bear. And other residents seem to have lost all sense of self-preservation as they walk out in front of her moving cruiser or sit placidly in the middle of a sharp bend in a mountain road. As she witnesses increasingly odd behavior and more bodies are discovered in baffling-and completely avoidable-circumstances, Officer Whittaker is dismayed to find no two cases are the same, except in their bizarreness. Though every possible explanation and conspiracy theory is considered, from mental breakdowns to aliens, it turns out to be something much more unsettling. The townsfolk are all losing their instincts, one by one. As the town descends into panic, and Mary's own instincts begin to fail, she must figure out what is happening, who is behind it, and how to prevent the quirky mountain village from turning into a ghost town"--